INDO-EUROPEAN COMMUNICATIONS:: THE MODEL OF “NOMADIC HOMELAND” - A. Novozhenov, Victor; K. Altynbekova, Elina; Zh. Sydykov, Aibek (Gênero & Direito, 2020)
The authors of the article studied the origin of Indo-European tribes in the light of ancient communications and the spread of the tribes according to wheeled transport relics in the steppe zone of Eastern Eurasia. The authors considered some modern theories related to Indo-European (IE) and Indo-Iranian (IIr) origin, defined IE innovations that marked the territories as possible homelands for IEs, and localized them on the map and. The authors used the method of mapping and analysing of IE innovations for localization of possible homeland teritories of IE on the maps and substantiate the polycentric model of the ancestral homeland of IE as model of “nomadic homeland”. According to this model, the IE homeland was localized in the steppe-lands of Eurasian continent, and in the course of time changed its place from Assyrian steppes to Eurasia (Europe and Ural-Kazakh steppes) by two main ways (north and south) through Margiana and Transcaucasia.